The funny little woman - Mosel, Arlene; Lent, Blair (New York : Puffin, 1986)
While chasing a dumpling, a little lady is captured by wicked creatures from whom she escapes with the means of becoming the richest woman in Japan.
Caldecott Medal/Honor.
School Library Journal.
Wilson's Children.
Booklist, February 2004.
Christian Library, November 2004.
Kirkus Review, October 2004.
Keywords: Folklore -- Japan; Folklore -- Japan